Mathematical Model Impact Analysis of a Real-Life Pre-exposure Prophylaxis and Treatment-As-Prevention Study Among Female Sex Workers in Cotonou, Benin - AFFOLABI, DISSOU (My University, 2021)
Daily pre-exposure prophylaxis (PrEP) and treatment-as-prevention (TasP) reduce HIV acquisition and transmission risk, respectively. A demonstration study (2015–2017) assessed TasP and PrEP feasibility among female sex workers (FSW) in Cotonou, Benin. Setting: Cotonou, Benin. Methods: We developed a compartmental HIV transmission model featuring PrEP and antiretroviral therapy (ART) among the high-risk (FSW and clients) and low-risk populations, calibrated to historical epidemiological and demonstration study data, reflecting observed lower PrEP uptake, adherence and retention compared with TasP. We estimated the population-level impact of the 2-year study and several 20-year intervention scenarios, varying coverage and adherence independently and together. We report the percentage [median, 2.5th–97.5th percentile uncertainty interval (95% UI)] of HIV infections prevented comparing the intervention and counterfactual (2017 coverages: 0% PrEP and 49% ART) scenarios. Results: The 2-year study (2017 coverages: 9% PrEP and 83% ART) prevented an estimated 8% (95% UI 6–12) and 6% (3–10) infections among FSW over 2 and 20 years, respectively, compared with 7% (3–11) and 5% (2–9) overall. The PrEP and TasP arms prevented 0.4% (0.2–0.8) and 4.6% (2.2–8.7) infections overall over 20 years, respectively. Twenty-year PrEP and TasP scale-ups (2035 coverages: 47% PrEP and 88% ART) prevented 21% (17–26) and 17% (10–27) infections among FSW, respectively, and 5% (3–10) and 17% (10–27) overall. Compared with TasP scale-up alone, PrEP and TasP combined scale-up prevented 1.9× and 1.2× more infections among FSW and overall, respectively. Conclusions: The demonstration study impact was modest, and mostly from TasP. Increasing PrEP adherence and coverage improves impact substantially among FSW, but little overall. We recommend TasP in prevention packages.
Keywords: FSW; PrEP; TasP; Benin; modeling; prevention